MAMMA MIA! Norwegian Midwives’ Practices and Views About Gestational Weight Gain, Physical Activity, and Nutrition - Haakstad, Lene A. H.; Mjønerud, Julie M. F.; Dalhaug, Emilie Mass (Frontiers in Psychology, 2020)
Objectives Most studies regarding prevalence of prenatal lifestyle counseling are based on patient report of provider advice. The aim of the present study was to describe midwives’ practice and views in promoting three distinct, but importantly related lifestyle factors: gestational weight gain (GWG), regular physical activity (PA), and nutrition. Design A cross-sectional study. Setting Healthcare clinics in Oslo and Akershus County, Norway. Participants Clinics that expressed interest to participate provided an email list of the midwives. Of 107 midwives invited to participate, 65 completed the 15-min electronic survey (SurveyXact), giving a response rate of 60.7%. Outcome Measures We developed a new questionnaire based on questions and results from similar studies, as no validated questionnaires existed when we initiated this project in 2014. The final electronic questionnaire included a mix of close-ended questions, semi–close-ended questions, and 11-point Likert scales and covered demographics, personal health behaviors, counseling practice, views, and self-perceived role in lifestyle counseling. Results Mean workload in prenatal care was 78%, and mean years practicing was 8.9 (±7.5). Across all three health topics, most (74–95%) reported to give advice on the first meeting, with a mean frequency of 2.2 (±1.4), 2.7 (±1.8), and 2.7 (±2.0) for GWG, PA, and nutrition counseling, respectively. Approximately 40% did not report advice on GWG or give advice discordant with the Institute of Medicine (IOM) recommendations (2009) for at least one prepregnancy body mass index (BMI) category. GWG was rated as more unpleasant to talk about than PA (3.0 ± 2.8 vs. 1.1 ± 2.5, p < 0.001) and nutrition (3.0 ± 2.8 vs. 1.2 ± 2.5, p = 0.002). Also, regarding the importance of giving lifestyle advice, PA (9.6 ± 0.9 vs. 8.3 ± 2.2, p < 0.001) and nutrition (9.9 ± 0.4 vs. 8.3 ± 2.2, p < 0.001) were rated as more important than advice about GWG. Postpartum, nearly 40% gave advice about PA, whereas only two (3.1%) reported to discuss weight/weight retention (p < 0.001). Conclusion While most midwives gave advice on GWG, PA, and nutrition at the first meeting and rated lifestyle counseling as an important topic, the advice on GWG was often discordant with IOM recommendations, and the topic was viewed as more unpleasant to talk about than PA and nutrition.